Enhancing power and fuel generation efficiency in solid oxide electrochemical cells via advanced electrode materials design - Fang, Liyang (Kansas State University, 2024)
Addressing the severe impacts of climate change necessitates a profound overhaul of our current energy system, which entails transitioning away from carbon-intensive fossil fuels and embracing low-carbon alternatives. This transformation involves a range of strategies, including deploying more renewable energy sources as well as adopting energy-efficient technologies, building sustainable infrastructure, and implementing policies that encourage the uptake of clean energy. By embracing clean energy alternatives, we can foster a more sustainable, resilient, and equitable future for all. The solid oxide electrochemical cells (SOCs) stand out as a highly promising clean energy technology that offers several benefits, showing significant potential to play a pivotal role in the transition towards a sustainable, low-carbon energy future. Intermediate temperature SOCs can convert fuels to electricity in fuel cell mode, and produce various fuels from renewable electricity working as electrolyzers. A key issue in the development of SOCs is the sluggish oxygen reduction reaction (ORR) and oxygen evolution reaction (OER). Double perovskite PrBa[subscript 0.5]Sr[subscript 0.5]Co[subscript 1.5]Fe[subscript 0.5]O[subscript 5+δ] (PBSCF) is known to have high oxygen mobility and excellent surface exchange properties at intermediate temperatures. And based on conventional PBSCF material, we successfully designed a hybrid electrode material which significantly enhanced the catalytic activities in the ORR/OER processes and drastically improved the performance. Our hybrid electrode showed great potential as a high-performance oxygen electrode for next generation intermediate temperature SOCs. CO² electrolysis is considered as another promising technology base for the development of sustainable energy systems, as it has the potential to facilitate the attainment of carbon neutrality. However, despite its potential, the electro-catalytic activity of the negative electrode in CO² electrolysis remains a challenge, thereby hindering its performance and commercial viability. As such, there exists a pressing need to develop a negative electrode characterized by high catalytic activity for CO² adsorption, dissociation, and reduction. Here we report a Ni and Co co-doping strategy to realize the in situ exsolution of Ni-Co alloy nanoparticles on the surface of Sm[subscript 0.2]Ce[subscript 0.2]O[subscript 2-δ] (SDC) as a cathode material for SOECs. The doping ratio of Ni-Co was optimized and its effect on physicochemical and electrochemical properties were systemically studied. Moreover, the synergetic effect of Ni-Co alloy was high lightened when compared to single metallic dopant. By tuning the dopant types and concentration, SOECs equipped with the optimized cathode, SDC doped with 25% Ni-Co (SDCNiCo25), achieved a superior current density of 2.7 A cm⁻² at 750 °C, 1.5 V.
Keywords: Solid oxide cells; Solid oxide fuel cells; Solid oxide electrolysis cells; CO2 electrolysis; Hydrogen production